Influence of biomimicry structures on ecosystem function in a Rocky Mountain incised stream. Issue 1 (26th January 2022) - Reinert, James Holden; Albertson, Lindsey K.; Junker, James R.
Abstract: Rising levels of stream degradation have motivated a boom in restoration projects across the globe. However, postrestoration monitoring is still frequently lacking and does not always incorporate biotic responses to changes in the physical template. Beaver mimicry structures (BMSs) are becoming a popular tool to restore degraded streams throughout the American West, but relatively little is known about how these installations influence both biotic and abiotic factors, with consequences for ecosystem functioning. We monitored basal resources, organic and inorganic material standing stocks, and macroinvertebrate density, biomass, and production to quantify functional responses to BMS installation. We compared conditions at BMS sites to naturally occurring beaver dam and reference riffle sites in a low‐gradient stream in southwest Montana. Thermal ranges were contracted, and daily maximum temperatures were higher, in the BMS treatment compared to the reference riffle treatment. Fine sediment standing stock and basal resources were similar in Beaver and BMS treatments, and both treatments were higher than reference riffles. All treatments differed in macroinvertebrate density, which was highest in the Beaver treatment, followed by Mimic and then Reference treatment. Biomass and secondary production were higher in Beaver and BMS treatments compared to the Reference treatment, but only Beaver and Reference treatments differed significantly, likely due to differences in physical habitat and basal resource availability. Consequently, production of collector–gatherers in the BMS treatment and shredders in the Beaver treatment was higher than in reference riffles. Changes to local hydrology and sediment dynamics resulting from BMS influence biotic functional responses like organic material standing stock and secondary production, creating habitat and ecosystem function distinct from riffles and similar to target conditions of natural beaver dams. To continue to improve BMS as a standard restoration practice, future research could consider the extent of degradation, increasing temporal scale of monitoring. Alterations to aquatic–terrestrial subsidies and impacts to fishes.